Morphological Characterization of Yardlong Bean for Pod Borer Infestation - Sultana, Nasrin Jahan; Das, Krishna Rany; Masum, Md. Abdullah Al; Ahmad, Masum (Fundamental and Applied Agriculture, 2024)
The yardlong bean is a popular vegetable among the people of Asia. However, pod borer infestation is one of the major setbacks of growing this vegetables. This insect not only reduce the yield of the crops, but also compromise the wulaity of the vegetable. Therefore, to devise an effective control measure, its characterization is important. In order to assess the resistance of several yardlong bean types to pod borer attacks, an experiment was conducted at the experimental farm of Bangladesh Agricultural University, located in Mymensingh, Bangladesh, from September 2022 to April 2023. The study included nine yardlong bean varieties. The experiment was arranged with five replications using a completely randomized design (CRD). Eighteen parameters including plant height, main branch, secondary branch, leaf number, flower number, fruit number and fruit color were used to distinguish and differentiate the nine fabaceae genotypes. Among the varieties, BARI Borboti Yardlong Bean-2 produced the highest yield of 98.57 g per plant. A comparison of the BARI Borboti-2 variety’s dry seed output and other characteristics showed that it had the highest total number of pods per plant (8.40), the lowest infestation rate (13%) by pod borers, and the maximum quantity of dry seeds (15 g). In most cases, the Lubna variety had the worst performance. The majority of the types had the second lowest infection infestation. According to the current investigation, BARI Yardlong Bean -2 showed the best performance and demonstrated better overall performance like flower color, pod color, length, breadth, and seed color varying among the varieties fewer pod borer infestations.